Community Needs Study in the Establishment of New Study Programs at STAB Negeri Raden Wijaya, Wonogiri, Central Java - Adi Nugroho Susanto Putro; Ari Mariyono; Sudarto Sudarto (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This research aims to analyze and formulate the steps involved in a community needs assessment (Needs Study) and to identify the most required new study programs with the potential for realization at the State College of Buddhist Studies (STAB Negeri) Raden Wijaya. This Needs Study was conducted through three main steps: Identification of Community Needs, Analysis of Internal and External Factors, and Formulation of Recommendations. The research findings indicate a significant demand from the Buddhist community in Indonesia for several non-traditional study programs, with the top five being: Computer Education (11.22%), Mandarin Language Education (9.65%), Early Childhood Education (8.36%), English Language Education (8.04%), and Guidance and Counseling (7.08%). Based on a comparison between community needs and the availability and readiness of Human Resources (HR) at STAB Negeri Raden Wijaya, four study programs are proposed for immediate establishment: English Language Education, Education Management, Educational Technology, and Indonesian Language and Literature Education. These four proposed programs possess a strong internal HR foundation, consisting of lecturers holding S2 (Master's) and S3 (Doctoral) degrees with specific expertise in the relevant fields, demonstrating the institution's readiness to quickly form core program management teams and teach essential courses.